L’économie circulaire, quels enjeux de développement pour les territoires ? - Amadou Niang; Sébastien Bourdin; André Torre (Développement Durable et Territoires, 2020)
The circular economy, a new economic model that respects the environment, alternative to the linear economy, is presented as an opportunity for territorial sustainable development. In the context of socio-ecological transition, its approaches are thus increasingly experienced locally but the question of their territoriality and their links with sustainable spatial development remains scientifically unstable. This article is a review of the bibliography which aims to analyze the territoriality of circular economy approaches and to assess if they can become an opportunity to ensure sustainable territorial development.